Microstructural heterogeneity and property variations in cast and vacuum hot-pressed CoCrPtB alloy - Li, Yan (2024)
Limited research has been undertaken regarding the homogeneity of CoCrPtB alloy billets. A CoCrPtB alloy was processed through casting and vacuum hot pressing. This investigation delved into the interconnection between the secondary dendrite arm spacing (SDAS) in the as-hot-pressed samples and their corresponding attributes, specifically Vickers hardness and magnetic properties. Systematic sampling was conducted on the cross-sectional layer and longitudinal surface. Upon examination of the cross-sectional layer proximate to the uppermost region of the hot casting, a discernible parabolic trend was observed for the SDAS that exhibited a gradual increment from the peripheral regions toward the central area along the width. Simultaneously, the fraction of the dendrite phase displayed a consistent linear decline, attaining its peak value at the central portion of the billet. Conversely, on the longitudinal surface, SDAS and the fraction of the dendrite phase remained fairly uniform within the same column sampling regions. However, a notable divergence was identified in the central section, characterized by an augmented SDAS and diminished dendrite phase content. This inherent microstructural inhomogeneity within the CoCrPtB alloy engendered discernible disparities in material properties.